Manajemen Neurogenic Pulmonary Edema pada Laki-laki Usia 60 Tahun dengan Stroke Infark Luas di RSUD Jendral A. Yani Kota Metro - M. Panji Bintang Gumantara; Halomoan Simon Tambunan (Medula, 2020)
Neurogenic Pulmonary Edema (NPE) is a pulmonary compromise condition due to severe damage of the central nervous system that causes symptoms similar to ARDS accompanied by pulmonary edema. NPE often occurs in traumatic brain injury (TBI), hemorrhage, recurrent seizures, and epilepsy. Stroke is a focal or general acute neurological deficit condition during more than 24 hours caused by cerebrovascular factors. In patient with extensive stroke infarction of the brain can cause suppression of the respiratory center in the brain so that stroke patients can get complications in the respiratory system that aggravate the patient's condition. This case report described a 60-year-old man with decreased consciousness and weakness of the left limbs since 6 hours before entering hospital with shortness of breath, reddish coughing phlegm, fever, rapid and shallow breathing. Management was given to the patient in pharmacological and non-pharmacological collaborative therapies. Intensive care was planned in the Intensive Care Unit (ICU) formechanical ventilator. The patient's prognosis in this case report wasad malam. The purpose of this case report is to find out the description of clinical problems, identify the risk factors as the cause and provide the best management for patients.